Natural detoxification of antibiotics in the environment: A one health perspective - Baquero, Fernando; Coque, Teresa M.; Martínez, José-Luis (Frontiers in Microbiology, 2022)
The extended concept of one health integrates biological, geological, and chemical (bio-geo-chemical) components. Anthropogenic antibiotics are constantly and increasingly released into the soil and water environments. The fate of these drugs in the thin Earth space (“critical zone”) where the biosphere is placed determines the effect of antimicrobial agents on the microbiosphere, which can potentially alter the composition of the ecosystem and lead to the selection of antibiotic-resistant microorganisms including animal and human pathogens. However, soil and water environments are highly heterogeneous in their local composition; thus the permanence and activity of antibiotics. This is a case of “molecular ecology”: antibiotic molecules are adsorbed and eventually inactivated by interacting with biotic and abiotic molecules that are present at different concentrations in different places. There are poorly explored aspects of the pharmacodynamics (PD, biological action) and pharmacokinetics (PK, rates of decay) of antibiotics in water and soil environments. In this review, we explore the various biotic and abiotic factors contributing to antibiotic detoxification in the environment. These factors range from spontaneous degradation to the detoxifying effects produced by clay minerals (forming geochemical platforms with degradative reactions influenced by light, metals, or pH), charcoal, natural organic matter (including cellulose and chitin), biodegradation by bacterial populations and complex bacterial consortia (including “bacterial subsistence”; in other words, microbes taking antibiotics as nutrients), by planktonic microalgae, fungi, plant removal and degradation, or sequestration by living and dead cells (necrobiome detoxification). Many of these processes occur in particulated material where bacteria from various origins (microbiota coalescence) might also attach (microbiotic particles), thereby determining the antibiotic environmental PK/PD and influencing the local selection of antibiotic resistant bacteria. The exploration of this complex field requires a multidisciplinary effort in developing the molecular ecology of antibiotics, but could result in a much more precise determination of the one health hazards of antibiotic production and release.